PENGARUH LATIHAN DRIBBLE DRILLTERHADAP KETERAMPILAN DRIBBLING PADA TIM SSB LASKAR BELIA DI KECAMATAN SIAK KABUPATEN SIAK - Hanafi Hanafi; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: In the game of football, variations and combinations are needed, one of which is the ability to dribble. This is in line with the player/testee's ability to dribble the ball at SSB Laskar Belia, Siak District, which shows that there are still deficiencies/errors in his dribbling technique. So that it will affect the ability to dribble for SSB Laskar Belia players. Therefore in this study the researchers used the Dribble drill training model as an improvement to improve the ability of players/testees to dribble the ball, in order to achieve the desired goals for SSB Laskar Belia players or coaches. This study aims to determine the effect of Dribble drill training on Dribbling skills in the SSB Laskar Muda team in Siak District, Siak Regency. The ability to dribble using dribble drills during the pretest and postest was good. Where the results of this study have also shown that there is an increase in dribbling ball skills on the SSB Laskar Muda team after carrying out Dribble drill exercises. This can also be seen from the average players and instrument norms, where the average increases by 1.10 seconds from the whole implementation. Meanwhile, from the test norm category, it can be seen that from good to very good. this is influenced by several factors including because they have long joined SSB Laskar Belia, so that their physical and endurance have formed by themselves, coupled with this dribble drill training.Keywords: Dribble Drill, Dribbling, Football